Psychometric Properties of the Career Adapt-Abilities Scale in Jordanian Society - Al Masoud, Hala F. (Dirasat: Educational Sciences, 2024)
Objectives: The purpose of this study is to investigate the psychometric properties of the Jordanian version of the Career Adapt-Abilities Scale, and to provide an Instrument for use in providing career counseling services in the Jordanian Society, to assist students in recognizing their abilities to meet the demands of careers and the requirements of the labor market. Methods: The Jordanian version of the Career Adapt-Abilities Scale was administered to a total of (259) bachelor's degree students enrolled in some scientific and humanities colleges at a public university and private university. An exploratory factor analysis was performed on the (24) items of the Jordanian version of the Career Adapt-Abilities Scale. Results: The results showed that the Jordanian version of the Career Adapt-Abilities scale demonstrates high levels of validity and reliability that align with the psychometric properties of the International scale. The current version of the scale is considered a suitable Instrument for measuring Career Adapt-Abilities by professionals in career counseling. Conclusions: The study recommends using the scale in conducting more future research in the field of counseling and career guidance in the Jordanian society. It also suggests verifying the psychometric properties of the Jordanian version of the Career Adapt-Abilities Scale on new samples and specializations, and at the level of postgraduate students in public and private Jordanian universities, as well as on samples of students at the end of the basic and secondary stages in general education.